Pengaruh Usia, Gender dan Kedekatan Tempat Tinggal dengan Landfill terhadap Kejadian Diabetes Melitus Tipe 2 - Nabilla Tita Saputri; Yusuf Alam Romadhon (Jurnal Sains dan Kesehatan, 2026)
Diabetes Mellitus is a non-communicable disease with an increasing prevalence and has become a major public health concern globally and nationally. The incidence of diabetes mellitus is influenced by various individual and environmental factors. This study aimed to analyze the relationship between age, gender, and residential proximity to landfill areas and the incidence of diabetes mellitus in Bendosari District. A quantitative analytic observational design with a cross-sectional approach was employed. The study population consisted of 1,890 patient visit records recorded in the Management Information System of Bendosari Public Health Center in 2025. A total of 363 respondents were selected using proportionate stratified random sampling. Data were analyzed through univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using multiple logistic regression. The findings showed that age was significantly associated with diabetes mellitus incidence (p=0.000; OR=79.790; 95% CI=53.511–118.974). Gender was also significantly related to diabetes mellitus incidence (p=0.000; OR=0.298; 95% CI=0.203–0.435), indicating that females had a higher risk than males. In contrast, residential proximity to landfill areas was not significantly associated with diabetes mellitus incidence (p=0.308; OR=1.247; 95% CI=0.439–3.540). Multivariate analysis revealed that age and gender were the dominant factors influencing diabetes mellitus incidence, with the model explaining 56.1% of the variation. The study concludes that age and gender are significant determinants of diabetes mellitus incidence, whereas residential proximity to landfill areas has not been proven to significantly affect its occurrence.